IMPROVEMENT OF METHODICAL APPROACHES TO THE MANAGEMENT OF THE SYSTEM OF ECONOMIC SECURITY OF BAKERY INDUSTRY ENTERPRISES - BONDARENKO-BEREHOVYCH, Valeriia (Theoretical and Practical Research in Economic Fields, 2021)
The article investigates the methods of improving the methodological approaches to the management of the economic security system of the bakery industry. It was found that the creation of such a system requires the intensification of scientific and practical research to improve the theoretical and methodological foundations of economic security systems that would take into account general and specific problems of the industry and were effective in both short and long term. The approaches to the definition of the concept of "economic security of the enterprise" are generalized and systematized and the author's definition of this category is given. The guidelines of the research within the system approach are determined. The components of the economic security management system of the bakery enterprises and their correlation are investigated and substantiated. A system of economic security management of enterprises of the bakery industry has been developed, which takes into account theoretical and methodological studies of systems theory and systems analysis in the field of economic security. Within the framework of the developed system, its main elements are studied and a conclusion is made about the peculiarities of its implementation and functioning.